Contesting Empires - Hart, J. author. aut Link
XVIII, 286 p.
Keywords: Based on extensive archival research, this book looks at the earlier contest of empires in the New World, especially among Spain, France and England, and then examines the opposition to empire, the promotion of empire and the question of slavery. Hart's discussion on slavery has even larger scope ranging from early Arab, African and Portuguese practices in Africa and beyond to the legal abolition of slavery in the British empire, the United States and elsewhere in the Nineteenth-century.